2015
DOI: 10.1038/ajg.2015.286
|View full text |Cite
|
Sign up to set email alerts
|

Covered Metallic Stents With an Anti-Migration Design vs. Uncovered Stents for the Palliation of Malignant Gastric Outlet Obstruction: A Multicenter, Randomized Trial

Abstract: OBJECTIVES:Previous studies reported comparable stent patency between covered self-expandable metallic stents (SEMS) and uncovered SEMS (UCS) for palliation of malignant gastric outlet obstruction (GOO). The aim of this study was to evaluate the efficacy and safety of the newly developed WAVE-covered SEMS (WCS), which has an anti-migration design, compared with UCS in gastric cancer patients with symptomatic GOO.METHODS:A total of 102 inoperable gastric cancer patients with symptomatic GOO were prospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 35 publications
0
51
1
17
Order By: Relevance
“…On the other hand, the rate of tumor ingrowth or overgrowth in CMS was significantly lower than for UCMS in all reports shown in Table 2, which is an advantage of CMS. However, the rates of re-intervention and stent patency between CMS and UCMS were similar in these reports except for that of Lee et al (27). Lee et al reported that the CMS group had a significantly longer cumulative duration of stent patency compared with the UCMS group (27), though all patients undergoing deployment of SEMS had gastric cancer.…”
Section: Adverse Eventsmentioning
confidence: 39%
See 3 more Smart Citations
“…On the other hand, the rate of tumor ingrowth or overgrowth in CMS was significantly lower than for UCMS in all reports shown in Table 2, which is an advantage of CMS. However, the rates of re-intervention and stent patency between CMS and UCMS were similar in these reports except for that of Lee et al (27). Lee et al reported that the CMS group had a significantly longer cumulative duration of stent patency compared with the UCMS group (27), though all patients undergoing deployment of SEMS had gastric cancer.…”
Section: Adverse Eventsmentioning
confidence: 39%
“…However, the rates of re-intervention and stent patency between CMS and UCMS were similar in these reports except for that of Lee et al (27). Lee et al reported that the CMS group had a significantly longer cumulative duration of stent patency compared with the UCMS group (27), though all patients undergoing deployment of SEMS had gastric cancer. Minata et al reviewed several studies about comparison between CMS and UCMS.…”
Section: Adverse Eventsmentioning
confidence: 39%
See 2 more Smart Citations
“…Therefore, some authors have recommended concomitant biliary drainage before covered SEMS placement bridging the AOV [19,28]. However, several studies have shown that the risk of developing jaundice after SEMS placement is quite minimal (0-3.4%), irrespective of whether a bare or covered stent is used, most likely because the bile can drain through the space between the stent and the duodenal wall [29][30][31]; the rate of jaundice after SEMS placement in our present study was only 4.0%. In addition, a recent study has found that the bilirubin levels after covered SEMS placement bridging the AOV were similar between patients with and without prior or concomitant biliary drainage [32].…”
Section: Discussionmentioning
confidence: 99%